Single‐cell dynamics of chromatin activity during cell lineage differentiation in Caenorhabditis elegans embryos - Zhiguang Zhao; Rong Fan; Weina Xu; Yahui Kou; Yangyang Wang; Xuehua Ma; Zhuo Du (Molecular Systems Biology)
Abstract Elucidating the chromatin dynamics that orchestrate embryogenesis is a fundamental question in developmental biology. Here, we exploit position effects on expression as an indicator of chromatin activity and infer the chromatin activity landscape in every lineaged cell during Caenorhabditis elegans early embryogenesis. Systems‐level analyses reveal that chromatin activity distinguishes cellular states and correlates with fate patterning in the early embryos. As cell lineage unfolds, chromatin activity diversifies in a lineage‐dependent manner, with switch‐like changes accompanying anterior–posterior fate asymmetry and characteristic landscapes being established in different cell lineages. Upon tissue differentiation, cellular chromatin from distinct lineages converges according to tissue types but retains stable memories of lineage history, contributing to intra‐tissue cell heterogeneity. However, the chromatin landscapes of cells organized in a left–right symmetric pattern are predetermined to be analogous in early progenitors so as to pre‐set equivalent states. Finally, genome‐wide analysis identifies many regions exhibiting concordant chromatin activity changes that mediate the co‐regulation of functionally related genes during differentiation. Collectively, our study reveals the developmental and genomic dynamics of chromatin activity at the single‐cell level.